Rasch model of the child perceptions questionnaire in multi-country data. (February 2020) - Stamm, Tanja A.; Omara, Maisa; Bakerc, Sarah R.; Foster Page, Lyndie; Thomson, William Murray; Benson, Philip E.; Broomhead, Tom; Aguilar-Diaz, Fatima; Do, Loc; Gibson, Barry J.; Hirsch, Christian; Marshman, Zoe; et al.
Graphical abstract: Abstract: Objective: To be fit-for-purpose, oral health-related quality of life instruments must possess a range of psychometric properties which had not been fully examined in the 16-item Short Form Child Perceptions Questionnaire for children aged 11 to 14 years (CPQ11-14 ISF-16). We used advanced statistical approaches to determine the CPQ's measurement accuracy, precision, invariance and dimensionality and analyzed whether age range could be extended from 8 to 15 years. Methods: Fit to the Rasch model was examined in 6648 8-to-15-year-olds from Australia, New Zealand, Brunei, Cambodia, Hong Kong, Malaysia, Thailand, Germany, United Kingdom, Brazil and Mexico. Results: In all but two items, the initial five answer options were reduced to three or four, to increase precision of the children's selection. Items 10 ( Shy/embarrassed) and 11 ( Concerned what others think) showed an 'extra' dependency between item scores beyond the relationship related to the underlying latent construct represented by the instrument, and so were deleted. Without these two items, the CPQ was unidimensional. The three oral symptoms items (4 Food stuck in teeth, 3 Bad breath and 1 Pain ) were required for a sufficient person-item coverage. In three out of 14 items (21 %), Europe and South America showed regional differences in the patterns of how the answer options were selected. No differential item functioning was detected for age. Conclusion: Except for a few modifications, the present analysis supports the combination of items, the cross-cultural validity of the CPQ with 14 items and the extension of the age range from 8 to 15 years. Clinical significance: The valid, reliable, shortened and age-extended version of the CPQ resulting from this study should be used in routine care and clinical research. Less items and a wider age range increase its usability. Symptoms items are needed to precisely differentiate between children with higher and lower quality of life.